STRENGTHENING STUDENTS' KNOWLEDGE OF CYBERBULLYING AT SMAN 12 PEKANBARU - Ahmad Jamaan; Muhammad Saeri; Fatmawati; Andrean Triatmaja; Ayu Iswandari; Deva Kanaya; Faisa Aufa Nabila; Melinawati; Muhamad Nazri; Muhammad Raja Athallah; Muhammad Ridho Azani; Vania Sheila Puspita; Wanda Fauzian Septa Indra (Jurnal Pengabdian Indonesia (JPI), 2026)
The development of digital technology has had a significant impact on the social lives of adolescents, including the emergence of cyberbullying issues that can disrupt mental health and social relationships. The current phenomenon suggests that adolescents are vulnerable to involvement as both perpetrators and victims, due to low literacy levels about cyberbullying. This community service activity aims to increase students' knowledge at SMAN 12 Pekanbaru about the dangers of cyberbullying and encourage them to use social media responsibly. This activity was conducted through interactive outreach and education, such as video screenings, discussion sessions, and role-plays involving students. The activity results demonstrated increased students' understanding of the impacts, causes, and preventive measures of cyberbullying. Furthermore, students showed enthusiasm for becoming anti-cyberbullying digital literacy agents in their schools and communities.